Effects of carnosine on the pro-antioxidative status of the anterior segment of the eye in experimental uveitis plus ocular hypertension (Ukrainian Journal of Ophthalmology, 2025)
Background: Finding means for improving the effectiveness of drug therapy of ocular inflammatory disorders, especially those with comorbidities, is a challenge to ophthalmology.Purpose: To assess the efficacy of carnosine for improving the pro/antioxidative imbalance in the anterior segment of rabbit eyes with experimental anterior uveitis in the presence of ocular hypertension (OHT).Material and Methods: Thirty-three rabbits were used in the study. Group 1 (the control group) comprised 9 intact rabbits and group 2, 12 animals with OHT induced prior to experimental non-infectious uveitis. Group 3 comprised 12 animals in which carnosine 5% was administered bilaterally into the conjunctival sac twice daily for four weeks for OHT induced prior to experimental non-infectious uveitis. Non-infectious uveitis was induced by injecting albumin into the anterior chamber, and OHT was induced by a single 0.1-mL injection of carbomer 0.3% into the anterior chamber. Activities of superoxide dismutase, catalase, glutathione peroxidase, NADH-oxidase and xanthine oxidase, and levels of total proteins and malondialdehyde (MDA) and diene conjugate (DC) in uveal tissue (iris and ciliary body) and aqueous humor specimens were determined.Results: Uveal activities of NADH-oxidase and xanthine oxidase were 19.4% (р < 0.05) and 27.2% (р < 0.01), respectively, lower in eyes of rabbits treated with carnosine than in eyes of animals not treated for anterior uveitis plus OHT. Uveal activities of glutathione peroxidase, superoxide dismutase and catalase were 34.7%, 39.6% and 28.4%, respectively, higher, and uveal MDA and DC levels were 39.3% and 33.3%, respectively, lower, in eyes of the former rabbits than of the latter rabbits. Similar changes were found in aqueous humor specimens of the experimental rabbits.Conclusion: Carnosine, when instilled locally, contributed to improvement in the pro/antioxidative imbalance in the anterior segment of rabbit eyes with uveitis plus OHT. It is reasonable to include carnosine-based eye drops into multiagent therapy of uveitis complicated by OHT due to their antioxidative, anti-inflammatory and membrane-stabilizing effects.
Keywords: non-infectious uveitis; ocular hypertension; antioxidative enzymes; peroxidation; carnosine